2019
DOI: 10.1371/journal.pone.0222715
|View full text |Cite
|
Sign up to set email alerts
|

Why are Chinese workers so unhappy? A comparative cross-national analysis of job satisfaction, job expectations, and job attributes

Abstract: Using data from the 2015 International Social Survey Program (ISSP), this study conducts a multinational comparison of job satisfaction determinants and their drivers in 36 countries and regions, with particular attention to the reasons for relatively low job satisfaction among Chinese workers. Based on our results from a Blinder-Oaxaca decomposition analysis, we attribute a substantial portion of the job satisfaction differences between China and the other countries to different job attributes and expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…This finding supports existing literature which states that culture can influence the relationship between job attributes and job satisfaction (e.g. Andreassi et al, 2012;Klassen et al, 2010;Kord and Tamini, 2012;Walga, 2018;Zhang et al, 2019). It also enriches the studies targeting cultural diversity in virtual team collaboration, which are considered complex (Han and Beyerlein, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding supports existing literature which states that culture can influence the relationship between job attributes and job satisfaction (e.g. Andreassi et al, 2012;Klassen et al, 2010;Kord and Tamini, 2012;Walga, 2018;Zhang et al, 2019). It also enriches the studies targeting cultural diversity in virtual team collaboration, which are considered complex (Han and Beyerlein, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Due to globalization, people from different cultures work together, and cross-cultural differences have become a relevant factor for virtual work-and job satisfaction research. Extant literature proposes that the relationship between job attributes and job satisfaction can vary across different cultures (Andreassi et al, 2012, Klassen et al, 2010Kord and Tamini, 2012;Zhang et al, 2019). Generally, two streams of research target these cross-cultural differences.…”
Section: Cross-cultural Differences and The Virtual Work Intensity: Job Satisfaction Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…More experienced and skilled doctors and nurses are likely to take more responsibilities and higher workloads, which might result in higher levels of BO and STS. Research has reported that Chinese workers value job security and a good income more than their counterparts in Western countries ( Zhang et al, 2019 ). Higher qualifications are likely to lead to higher income.…”
Section: Discussionmentioning
confidence: 99%
“…Highly satisfied workers are typically more reliable and punctual, quite productive, more devoted, and happier in their personal lives [ 6 ]. Employees should be given opportunities for advancement for this reason, such as pay scales, employee participation in policy-making, and making attempts to boost organizational commitment [ 7 ]. The nature of the job, the way in which it is supervised, job security [ 8 ], recognition, and development are crucial factors for employees’ organizational commitment.…”
Section: Introductionmentioning
confidence: 99%